Macromolecular properties of cepacian in water and in dimethylsulfoxide - Herasimenka, Yury; Cescuttia, Paola; Noguera, Carlos E. Sampaio [UNESP]; Ruggiero, José Roberto [UNESP]; Urbani, Ranieri; Impallomeni, Giuseppe; Zanetti, Flavio; Campidelli, Stphane; Prato, Maurizio; Rizzo, Roberto (Elsevier B.V., 2008)
Cepacian is the exopolysaccharide produced by the majority of the so far investigated clinical strains of the Burkholderia cepacia complex. This is a group of nine closely related bacterial species that might cause serious lung infections in cystic fibrosis patients, in some cases leading to death. In this paper the aggregation ability and the conformational properties of cepacian chain were investigated to understand its role in biofilm formation. Viscosity and atomic force microscopy studies in water and in mixed (dimethylsulfoxide/water) solvent indicated the formation of double stranded molecular structures in aqueous solutions. Inter-residue short distances along cepacian chain were investigated by NOE NMR, which showed that two side chains of cepacian were not conformation ally free due to strong interactions with the polymer backbone. These interactions were attributed to hydrogen bonding and contributed to structure rigidity. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Exopolysaccharide; Burkholderia cepacia complex; biofilm; conformational properties; dimethylsulfoxide solutions